Anton's dance class - Du Beke, Anton
For each of the five Ballroom dances and five Latin dances, Anton describes the history and origins of the dance, and illustrates his pithy text with step-by-step photography and glorious action shots from the past. He then gives easy-to-follow instruction to help you do those steps at home or in dance class. And this is all captured on a dynamic DVD too, demonstrating the steps of four of the individual dances